2022
DOI: 10.3389/fnut.2021.799709
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D and Influenza: Meta-Analysis and Systematic Review of Randomized Controlled Trials

Abstract: Background: Vitamin D supplementation improves the immune function of human body and can be a convenient way to prevent influenza. However, evidence on the protective effect of vitamin D supplementation on influenza from Randomized Controlled Trials (RCTs) is inconclusive.Methods: RCTs regarding the association between vitamin D supplementation and influenza were identified by searching PubMed, Cochrane library, Embase and Chinese Biomedical Database (CBM) from inception until present (last updated on 10 Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Besides TB, the relationship between vitamin D and acute respiratory infections (ARIs) has also been extensively discussed ( Figures 4 , 5 ). Several studies of RCTs reveal that vitamin D supplementation has a protective effect against influenza ( 46 , 47 ). The sixth-ranked highly cited article (presented in Table 2 ) showed that serum 25(OH)D levels were inversely associated with acute upper respiratory tract infection ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides TB, the relationship between vitamin D and acute respiratory infections (ARIs) has also been extensively discussed ( Figures 4 , 5 ). Several studies of RCTs reveal that vitamin D supplementation has a protective effect against influenza ( 46 , 47 ). The sixth-ranked highly cited article (presented in Table 2 ) showed that serum 25(OH)D levels were inversely associated with acute upper respiratory tract infection ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews on vitamin C suggest that preventative benefits may be dependent on gender (males), environmental conditions and certain stressors an individual may be exposed to; this will require future attention [ 66 , 67 , 68 ]. A number of systematic reviews have looked at vitamin D, especially since the COVID-19 pandemic [ 67 , 78 , 80 , 81 , 82 , 83 ]. Sub-group analyses have shown that vitamin D may be beneficial as a daily dose over a short-term, but for which individuals with which baseline levels or involving what stressors is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Low vitamin D status is associated with poorer outcomes following acute respiratory diseases including influenza [ 1 ]. Vitamin D supplements are touted as being useful in high doses for reducing the severity of seasonal influenza [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%